Optimization of the homogenization and hot isostatic pressing heat treatments of a fourth generation single crystal superalloy - Caron Pierre; Ramusat Catherine (MATEC Web of Conferences, 2014)
Various solution heat treatment sequences including a hot isostatic pressing step were tested on the MC-NG fourth generation single crystal superalloy with the aim to minimize the total duration of the treatment while obtaining a satisfactory level of microstructural homogeneity and low amount and size of pores. A procedure including the HIP step after full solutioning of the material allows to avoid reopening of the pores but needs a short post-HIP heat treatment followed by air quenching to get the desired γ′ precipitate size. The total duration of the solution heat treatment has been reduced from 18 to 6 hours as compared with the previous standard procedure.